Role of Omega-3 Acids in Cardiovascular Health: A Literature Review - Laksono, Sidhi; Hosanna, Cliffian (JURNAL KESMAS DAN GIZI (JKG), 2024)
Introduction: Cardiovascular disease (CVD) is the leading cause of death in the world, with 27% of deaths in 2020 attributable to CVD. American Heart Association recommends adopting Mediterranean diet and eating 2-3 servings of fish to increase cardiovascular health and decrease morbidity and mortality caused by CVDs. This effect is thought to be attributed to Omega-3 content in those diets. But, conclusive evidence about the role of Omega-3 in cardiovascular disease hasn’t been reached. This paper aims to discuss further on to the topic of effects of Omega-3 on cardiovascular health. Method: Searching PubMed using keywords “Omega-3 Fatty Acids” AND “Cardiovascular”, and filtering relevant journals. Results: A literature review will be made from 6 choosen RCTs that fulfill all the criteria. Discussion: Bhatt et al concludes that supplementation of icosapent ethyl decreases CVD mortality, non-fatal MI, non-fatal stroke and unstable angina by 25%. But other RCTs fail to demonstrate said effects. Studies by Bowman et al, Kalstad et al, Manson et al, Nicholls et al, and Roncaglioni et al. concludes that supplementation of omega-3 fatty acid does not produce a significant change in CVD. These different findings across different studies may be caused by different doses of Omega-3 given, different baseline characteristics of patients and medications that masks the effects of Omega-3. Conclusion: Further studies are needed to determine the effects of omega-3 in CVD, but consumption of omega-3 appears to be safe and shows a slight reduction in CVD events based on a recent meta-analysis by Bernasconi et al.